VERBA TRANSITIF DALAM THREAD HOROR DI TWITTER @DARJOFESS - Selvia Parwati Putri; Najiibah (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2022)
This study discusses the production of transitive verbs, types of transitive verbs, the role of transitive verbs, and their grammatical meanings found in the horror thread on the Twitter account @darjofess. The horror thread that will be analyzed is entitled “An Strange Experience on the South Beach of Malang” which was uploaded on April 19, 2022. The research method used in this research is descriptive qualitative research and literature study. The data collection technique in this study was a read-note technique, and documentation in the form of screenshots which were then listened to intensively. The aims of this study are: 1) To find out the types of transitive verbs in the object of study in the form of a horror thread on Twitter and social media; 2) Knowing the type of transitive verb role in the object of study in the form of a horror thread on Twitter social media. The results of this study indicate there are 27 transitive verbs dominated by affix composition (meN-), that is mem-, meng-, meny-, men-, me-; 17 monotransitive verbs and 10 dwitransitive verbs are found, the role of predicate function filler in transitive verbs which is found entirely is the role of action